FACTORS AFFECTING LOCAL CASSAVA PRODUCTION JALAK TOWO IN KARANGANYAR REGENCY - Maria Vegasari Dian Puspita; Umi Barokah; Agustono Agustono (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2021)
Cassava is one of Indonesia's local food which ranks third largest after paddy and corn. CentralJava Province ranks second in producing cassava in Indonesia. One of the regencies / cities that has thepotential to be developed in cassava farming is Karanganyar Regency. Karanganyar Regency has acassava variety called Jalak Towo. Jalak towo has a softer texture compared to other cassava.Thisstudy aim were determine the factors of production that affect the production of jalak towo cassava inKaranganyar Regency and its optimization analysis. The basic method used in this research wasdescriptive and analytical methods. The research location was Tawangmangu Subdistrict and JatiyosoSubdistrict as sub-districts producing jalak towo cassava in Karanganyar Regency. Sampling in thisstudy using a random sampling method with a total of 60 respondents consisting of 30 people at eachlocation. Data analysis methods used include: cobb-douglas production function analysis, varyingmodel parameter analysis and optimization analysis. The results of this study indicate that the factorsthat influence the production of jalak towo cassava are land area, experience, manure, urea fertilizer,age of the farmer, and location. Production factors that affect cassava production from the analysis ofvarying model parameters in Kec. Tawangmangu is the area ofland, manure, urea fertilizer, age of the farmer, and labor, while in Kec. Jatiyoso is land area and age. The results of the optimization analysisshowed that the combination of the use of production factors in Tawangmangu and Jatiyoso Subistrictsware not optimal.